Estrés y grado de satisfacción laboral en el personal de enfermería. instituto regional de enfermedades neoplásicas - Novoa Jacobo, Danti Michael (2019)
The present descriptive-correlational quantitative research, of cross-section, was applied in the surgical center service of the Regional Institute of Neoplastic Diseases, during the months of April to August of 2017; in order to determine the relationship between the level of stress and job satisfaction of the nursing staff. The sample universe consisted of 25 nurses, who met the established inclusion criteria. The instruments used were Questionnaire to determine the level of stress elaborated by Maslach and Jackson (1986), and the Job Satisfaction Questionnaire prepared by Palma (1999). The results were presented in simple tables and double entry. For the statistical analysis, the Chi square statistical test (x2) was used. The conclusions were: 72 percent of the nurses presented moderate stress, 24 percent severe stress and four percent mild stress. Job satisfaction was 52 percent average for nurses, 40 percent high, and 8 percent low. The level of stress of the nursing staff is significantly related to the degree of job satisfaction.